تأثير الرتينول على إحداث التشوهات الجنينية: نظرة على المخاطر المرتبطة بفيتامين A في فترات الحمل (Journal of the College of Basic Education, 2025)
This study aimed to identify the effect of retinol on the occurrence of fetal malformations by describing and analyzing the reality of the specialty. This research deals with the relationship between retinol and the occurrence of fetal malformations, highlighting the mechanism of action and the recommended doses for pregnant women, with a statement of the founding of a positive correlation between the use of retinol and the occurrence of congenital malformations. The main risks of its use during pregnancy were distinguished, when its use should be stopped before pregnancy, and how to use it after pregnancy, with a statement of the recommended doses for each period and an explanation of the side effects of its use.